Analisis Implementasi Kebijakan Insentif Pajak Penghasilan Pasal 21 Ditanggung Pemerintah Di Masa Pandemi Covid-19 Pada Kpp Pratama Jakarta Pademangan Tahun 2020 - Nuke Nur Priyatin; Notika Rahmi (Jurnal Pajak Vokasi (JUPASI), 2022)
The outbreak of Corona Virus Disease 2019 (Covid-19) in Indonesia has had a significant impact on various sectors, one of which is the economy, such as the large number of layoffs and companies that are threatened tostop operating. In order to improve the people’s economy and restore the national economy, the government issued an Article-21 income tax incentive policy. The purpose of this study was to determine the implementation of the Article-21 Income Tax Incentive, the obstacles in the implementation of the incentive policy and the efforts made to overcome these obstacles. The research method used is descriptive qualitative method. The data sources consist of primary data in the form of interviews and secondary data in the form of tax revenue data, Article-21 Income Tax Revenue data, data on taxpayers who apply for Article-21 Income Tax Incentives, and data on taxpayers receiving Article-21 Income Tax Incentives. The results of this studyindicate that the implementation of Article 21 income tax incentive policy is running well, but there are still problems in communication and disposition. In terms of communication, the role of taxpayers is still less active, while in terms of disposition, supervision of taxpayers is also still lacking. Efforts that must be taken to overcome the existing obstacles are for tax officials to continue to communicate and improve supervision to prevent the possibility offraud.